PUBLIC ENGAGEMENT AND VISUAL DATA: THE POSSIBILITIES AND LIMITATIONS OF DEVELOPING PHOTOGRAPHIC EXHIBITIONS. (11th November 2018) - Martin, W; Pilcher, K
Abstract: A key focus for research is to promote impact and enhance public engagement by communicating our research findings with multiple and diverse audiences. Towards the end of an ESRC funded project 'Photographing Everyday Life: Ageing, Lived Experiences, Time and Space' we created and disseminated our key findings via an interactive photographic exhibition. The focus of the project was to explore the significance of the ordinary and day-to-day and focus on the meanings, lived experiences, practical activities, and social contexts in which people in mid to later life live their daily lives. The research involved a diverse sample of 62 women and men aged 50 years and over who took photographs of their different daily routines to create a weekly visual diary. This diary was then explored through in-depth photo-elicitation interviews to make visible the rhythms, patterns and meanings that underlie habitual and routinised everyday worlds. Within the photographic exhibitions we created a series of installations, mosaics, photographic images and digitised displays with the aim to portray our research findings on daily life in an interactive, creative and engaging way. We also collected ideas, images, insights and feedback from audiences who interacted with the exhibition. The photographic exhibition has since been presented at a wide range of venues including Brunel University London, Uxbridge Library, the British Library and at a number of conferences. This paper will conclude by reflecting on our experiences as well as the possibilities and limitations of disseminating social science data via the arts and humanities.